A STUDY OF HEAVY METALS OF BIOACCUMULATION IN SOME TISSUES Labeo Rohita FISH FROM HASDEO RIVER EFFECTS OF HEAVY METALS ON FISH - Saxena, Amita; Singh, R. K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the bioaccumulation of heavy metals in various tissues of fishes collected from the Hasdeo River in order to assess the ecological and health risks associated with the river’s water quality. A diverse range of fish species was sampled from multiple locations along the Hasdeo River, a major tributary of the Mahanadi River in India. Tissues from these fishes, including muscle, liver, gills, and skin, were analyzed for the presence and concentration of heavy metals, including lead (Pb), cadmium (Cd), mercury (Hg), and arsenic (As). The study employed advanced analytical techniques such as atomic absorption spectrometry and spectroscopy to determine metal concentrations. The results indicate significant variations in heavy metal concentrations among fish species and tissue types. The liver and gills showed higher metal accumulation than muscle and skin tissues. Additionally, the study found that the heavy metal levels in Labeo rohita fish from the Hasdeo River exceeded the permissible limits set by regulatory authorities, signifying a considerable threat to both aquatic life and the human population that relies on the river for sustenance.